Band tillage with fertilizer application for unpuddled transplanting rice in northeast of China - Sarker, Khokan Kumer; Chunlin, Xu; Xiaoyan, Wang; Minjin, Li; Lianhao, Li; Guiming, Liu (International Journal of Agricultural and Biological Engineering, 2016)
Many technological innovations have been developed in agriculture for rice cultivation. Farmers still rely on intensive soil tillage, broadcasting fertilizer, excess irrigation water and labor for rice production. Rice cultivation under unpuddled condition in band-tillage (BT) is a new alternative rice cultivation system in the regions where rainfall, fresh water resources, fertilizers and labors are limited. Therefore, the concept of inter-row BT (T-shaped) with row fertilizer application in soils for unpuddled transplanted rice cultivation (T1) was carried out at Fangzheng, Harbin in the northeast of China. The improved system (T1) was compared with traditional practices (T2) in randomized complete block design with three replications. T2 was done with removal of crop residue, full tillage, broadcasting fertilizer and puddled soils by using the conventional machine. Test results showed that all parameters were satisfied and met the requirements of agronomic performances. The variations of fertilizing stability and evenness were 1.84% and 1.72%, respectively. Soil cone penetration resistance was less in T1 than T2 after tillage. Irrigation water was saved by 26.3% in treatment T1 as compared with T2 for wet land preparation, and wet soil resistance depth had no significant difference. Planting depth was significantly different between the treatments which was affected by intensive tillage and puddling in T2 as compared with T1. Soil temperature was nearly similar, but comparatively 0.23°C (on average) higher than traditional system throughout the crop growing season. Crop growth rate and grain yield increased by 8.5% and 5.3%, respectively in band till with fertilizer placed compared to conventional practices of puddled transplanting. The unit production cost (￥/kg of grain yield) was found lower by 12.3% in treatment T1 than T2. The output-input ratio was marginally greater in treatment T1 (1.51) as compared to T2 (1.32). Short-term findings suggest that inter-row BT system with row fertilizer application could be used in unpuddled rice farming system instead of traditional puddled rice cultivation.Keywords: conservation agriculture, tillage system, unpuddled rice, irrigation, water saving, economicsDOI: 10.3965/j.ijabe.20160904.1673Citation: Sarker K K, Xu C L, Wang X Y, Li M J, Li L H, Liu G M. Band tillage with fertilizer application for unpuddled transplanting rice in northeast of China. Int J Agric & Biol Eng, 2016; 9(4): 73－83.